Potret Tata Kelola Ekonomi Hijau dalam Pembangunan Berkelanjutan di Indonesia Timur - Syamsul Bahri Abd. Rasyid; Misran; Herdin Arie Saputra (Research and Development Agency Ministry of Home Affairs, 2024)
Despite its potential benefits to humanity, the green economy fails to ensure an optimal balance and is instead a political concern. The global crisis includes climate disasters and is characterized by climate change, biodiversity loss, massive deforestation, administrative challenges, and other ecological damage. These exacerbate concerns for the environment, society, and economic balance. However, public understanding of green governance is lacking in Southeast Asia, which is considered a potential obstacle to public consensus on forest-dependent interests. Media coverage of forest governance is considered an important source of information in shaping public opinion as it generates digital representations. This study aims to investigate the presence of green economic governance in sustainable development in online news articles through content analysis of media coverage. Over two years (01/01/2020-01/01/2022), researchers collected Indonesian-language articles using the NCapture feature of NVivo 12 Plus, specifically focused on the topic